Analysis of The Effect of Technology Adaptation, Market Orientation, and Networking on Competitive Advantages and Business Performance of Batik UMKM in Laweyan, Solo, Central Java - Andre, Rahardian; Raharjo, Susilo Toto (Master of Management Diponegoro University, 2020)
The phenomenon that will be analyzed in this research is that the current development raises the urgency that there is a need for more effective and efficient performance that can increase productivity, increase profits and reduce costs. Batik MSMEs in Laweyan, Solo, Central Java, which currently mostly use manual and semi-manual methods, need to develop themselves in order to be able to compete with batik invaders from abroad such as Malaysia, China and Vietnam. The purpose of this study was to analyze the effect of technology adaptation, market orientation and networking on the competitive advantage and business performance of batik MSMEs in Laweyan, Solo, Central Java. The population chosen in this study were all of the Batik Laweyan UMKM as many as 156 UMKM Batik. The number of respondents used in this study was 156 Laweyan Batik UMKM. The sampling technique in this research is the census method. The data collection method is by using a questionnaire. The data analysis method used is Structural Equation Modeling. Based on research, market orientation has a positive effect on competitive advantage, adaptation of modern technology and networking has no effect on competitive advantage. Adaptation of modern technology, market orientation, networking and competitive advantage have a positive effect on business performance. In terms of testing the fit model, it states that the model has a good fit. So from this it can be concluded that the model has a good enough fit to predict business performance.